2017
DOI: 10.5469/neuroint.2017.12.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Alberta Stroke Program Early CT Score in the Prognostication after Endovascular Treatment for Ischemic Stroke: A Meta-analysis

Abstract: PurposeThe Alberta Stroke Program Early CT Score (ASPECTS) was devised to quantify the extent of early ischemic changes in the middle cerebral artery territory on brain CT. We performed a systematic review and meta-analysis of studies that presented clinical outcomes and baseline ASPECTS in ischemic stroke patients managed with endovascular methods to validate the use of ASPECTS for risk prognostication.Materials and MethodsWe searched the MEDLINE, EMBASE, and Cochran databases for observational or interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 34 publications
0
9
1
1
Order By: Relevance
“…20,21 With slightly older patients than in the EVT studies, 15 the GSR-ET will provide insights in the role of EVT in older patients in Germany. Higher ASPECTS is a known predictor of good outcome in EVT of large vessel occlusion stroke, 22 and the benefit of EVT in patients with low ASPECTS score is uncertain. 23 Finally, the question of efficacy of direct EVT versus EVT with prior IVT has been raised.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 With slightly older patients than in the EVT studies, 15 the GSR-ET will provide insights in the role of EVT in older patients in Germany. Higher ASPECTS is a known predictor of good outcome in EVT of large vessel occlusion stroke, 22 and the benefit of EVT in patients with low ASPECTS score is uncertain. 23 Finally, the question of efficacy of direct EVT versus EVT with prior IVT has been raised.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike IVT, meta-analyses showed that high ASPECTS favored a good clinical outcome after endovascular therapy in comparison with low ASPECTS. 19 However we did not find any significant association between ASPECT score and cf DNA level, probably because DNA release at cellular level may not be linearly reflected in early CT imaging. We performed baseline plain CT ASPECT scoring, not MRI ASPECT scoring.…”
Section: Discussioncontrasting
confidence: 65%
“…CT has the advantage of being a simple technique and can spare time for early treatment and fast intervention if needed. The baseline ASPECTS is a reliable predictor of the prognosis in patients with AIS [ 28 ]. ASPECTS has been included in the decision-making and assessment of neurovascular interventions in patients with AIS [ 3 ].…”
Section: Discussionmentioning
confidence: 99%